Transitional Patterns of Adolescent Females in Non-traditional Career Paths - Ciccocioppo, Anna-Lisa; Stewin, Leonard L.; Madill, Helen M.; Montgomerie, T. Craig; Tovell, Dorothy R.; Armour, Margaret-Ann; Fitzsimmons, George W. (Canadian Journal of Counselling and Psychotherapy, 2007)
In this study, focus groups (n = 13) were utilized to examine the factors that affected the career decision-making of adolescent females and young women in undergraduate science, engineering, and technology programs. The 51 participants included students from colleges, technical institutes, and universities in Alberta. Qualitative analysis (cf. Vaughn, Schumm, & Sinagub, 1996) was used to uncover seven themes: (a) transition from high school, (b) educational influences, (c) family influences, (d) academic issues, (e) coursework management, (f) gender issues, and (g) creating a successful student environment. Implications for career development theory, education, counselling, and for future research are discussed.